Challenges in adopting the industrialised buildling system modular system (IBMS) in the Malaysia's construction industry - Muhammad Nizam, Shahira Irdina (2022)
Industrialised Building System Modular System (IBSMS) can substantially raise the quality by shifting the work process from site to off-site and decreasing the construction period. It effectively contributes to sustainability in construction by lessening the disruption on-site, decreasing generated waste and reducing noise pollution. Yet modular systems are unable to be introduced effectively and properly with the scarcity of research thus the pace and achievement of modular systems in Malaysia are slower compared to other countries. The primary goal of this research is to identify the benefits, challenges and recommend possible solutions in adopting the IBS Modular System in Malaysia's construction industry. In this research, it mainly quantitative by using questionnaire survey approach which was filled by 77 industry professionals from G7 contractor company in Selangor. The result suggested that 41.6% percent of survey participants worked with 0-5 modular projects throughout their careers. 68.8% percent of the participants claimed that they did not involve with the modular project in the past 12 months whereas 68.8% percent claimed that they were involved with one or more modular projects in the past 5 years.